Examining The Effect of Educational Level and Job Suitability on Employment Sector in Cirebon City - Syaeful Bakhri; Aji Priambodo; Agustina (Journal of Global Business and Management Review, 2024)
This research analyzed survey data from 204 Cirebon City residents to investigate the associations between education level, job suitability, and employment sector. Education was classified as primary, secondary, high school, or university education. Job suitability compares respondents’ education to the typical qualifications needed for their current role. Outcomes included the sector of employment in fields such as services, manufacturing, finance, technology, and others. The results showed that higher education levels and greater alignment between schooling and occupation were associated with more employment in high-skilled sectors, such as finance and technology. Those with a university education and high education-job match tended to work in professional sectors. The findings indicate strong links between academic credentials, the occupational relevance of education, and securing jobs in skilled sectors. This study provides insights that can help shape policies that promote schooling and employment congruence.